Implementasi Kurikulum 2013 Dalam Meningkatkan Proses Pembelajaran Pendidikan Agama Islam Di Madrasah Aliyah Negeri Bitung - Musyafiah, Sarini; Zamroni, Afif (Ali Muchasan, 2020)
This study aims to analyze and describe the implementation of the 2013 curriculum in improving the Islamic education learning process in MAN 1 Bitung. This study used qualitative research methods. In this study, the authors used unstructured interviews to obtain information from informants. As for this research, the primary data sources are the Head of Madrasah, Waka Curriculum, SKI Teachers, Akidah Akhlak Teachers, Fiqh Teachers, and Hadith Al-Quran Teachers. Data analysis is used as follows: data collection, data identification, then the data is presented in the form of pictures, charts and so on to draw conclusions. Techniques for data validity were data checking, data checking, and testing of research results. The results show that the implementation of the 2013 curriculum in MAN 1 Bitung, including: (1) Implementation of K 13 in MAN 1 Bitung can be said to be efficient by utilizing IT media, (2) Involving all curriculum components, (3) it needs to be balanced with the ability of teachers ( 4) The teacher's lack of understanding of the scientific approach. (5) Using a religious approach in shaping the character of students, (6) Online-based learning